2020
DOI: 10.24021/raac.v18i1.5350
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizers on the root of Avena strigosa and behavior of Folsomia candida

Abstract: The aim of this work was to evaluate the effects of increasing doses of mineral and organic fertilizers on the root chemotaxis of Avena strigosa and avoidance of Folsomia candida. Five soil samples were used for the mineral fertilization with NPK and other five soil samples were used for the organic fertilization with poultry litter-based organic fertilizer. The experiment included control soils (without applications) and soils containing 4-, 8-, 16- and 32-ton fertilizer per ha. A. strigosa was planted and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The Collembola group is very sensitive to the effects of soil management practices, temperature, and moisture (Oliveira Filho and Baretta, 2016;Daghighi et al, 2017;Rousseau et al, 2019). Application of high poultry litter-based organic fertilizer doses in the soil can increase the toxic effects on Collembola (Baretta et al, 2021). Another study showed that fertilization with pig slurry stimulates the population of Collembola in comparison to the poultry litter (Silva et al, 2019).…”
Section: Response Of the Soil Fauna Community To Soil Management Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Collembola group is very sensitive to the effects of soil management practices, temperature, and moisture (Oliveira Filho and Baretta, 2016;Daghighi et al, 2017;Rousseau et al, 2019). Application of high poultry litter-based organic fertilizer doses in the soil can increase the toxic effects on Collembola (Baretta et al, 2021). Another study showed that fertilization with pig slurry stimulates the population of Collembola in comparison to the poultry litter (Silva et al, 2019).…”
Section: Response Of the Soil Fauna Community To Soil Management Systemsmentioning
confidence: 99%
“…It is important to emphasize that the management of organic fertilizer (poultry litter) must be carried out carefully, considering the size of the area and the amount of fertilizer. Ecotoxicological studies have shown that high doses of poultry litter can be highly toxic to Collembola (Maccari et al, 2020;Baretta et al, 2021). On the other hand, when used in conjunction with other management practices (NPK fertilization and cover crops), it can favor the soil invertebrate community.…”
Section: Response Of the Soil Fauna Community To Soil Management Systemsmentioning
confidence: 99%